An investigation into TOEIC listening comprehension problems of non-English major students - Phạm, Hồng Nhung (ĐHNN, 2017)
Listening skills are important for face-to-face communication, meetings, conferences,telephone conversations , etc.Being able to listen well is an important part of communication for everyone, especially for students. A student with good listening comprehension skills will be able to participate more effectively in communicative situations. Out of all the different tests offering to certify the level of English, the TOEIC is the simplest and most practical in terms of its contents, its format, and the rapidity of results. .